2014
DOI: 10.4045/tidsskr.13.1550
|View full text |Cite
|
Sign up to set email alerts
|

Legemiddelinteraksjoner hos pasienter i sykehjem

Abstract: The incidence of serious drug-drug interactions among nursing home patients in Trondheim Municipality is low. Polypharmacy is widespread, and the incidence of drug interactions where precautions should be taken is high. As nursing home patients are a vulnerable group with respect to drug interactions, the risk of interactions should be carefully considered when treatment with a new drug is started.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 23 publications
1
7
2
Order By: Relevance
“…The lower prevalence of DRPs as compared to other Norwegian studies reporting 2.5–3.5 DRPs/patient [ 1 , 12 , 13 ], might be related to more staffing with full-time rather than part-time physicians in Oslo and an increased focus in recent years on safer prescribing practice for the elderly. The average number of drug used per patient before the MR compares well or is slightly lower than in other studies reporting 6.1–9.8 regular [ 1 , 4 , 5 , 13 , 16 , 20 , 24 , 25 ] and 2.8–3.8 prn drugs [ 4 , 20 ]. The high drug utilization at NHs may also partly reflect that the drug regiments are based on guidelines developed for younger patients with less comorbidity and the lack of consensus on best practice for pharmacotherapy in the oldest old.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The lower prevalence of DRPs as compared to other Norwegian studies reporting 2.5–3.5 DRPs/patient [ 1 , 12 , 13 ], might be related to more staffing with full-time rather than part-time physicians in Oslo and an increased focus in recent years on safer prescribing practice for the elderly. The average number of drug used per patient before the MR compares well or is slightly lower than in other studies reporting 6.1–9.8 regular [ 1 , 4 , 5 , 13 , 16 , 20 , 24 , 25 ] and 2.8–3.8 prn drugs [ 4 , 20 ]. The high drug utilization at NHs may also partly reflect that the drug regiments are based on guidelines developed for younger patients with less comorbidity and the lack of consensus on best practice for pharmacotherapy in the oldest old.…”
Section: Discussionsupporting
confidence: 72%
“…However, we consider the validity of the results to be reasonable high because 82% of all NHs included 61% of all long-term care patients in the municipality, and because terminal illness was the only exclusion criterion. Furthermore, the patients’ age and sex distribution correspond well with that of the total NH population in the city and country [ 4 , 12 , 13 , 20–22 ]. Similar MR procedures at the various sites were ensured through training of the MR teams, standardized tools and classification systems [ 8–11 ] and because each pharmacist participated in several hundred MRs.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…There is also an increased risk of fall injuries and errors due to multiple medication and potential drug interactions [14, 15]. Studies by Soraas et al (2014) and Gulla et al (2016) found that the use of eight or more drugs is frequent in Norwegian nursing homes, leading to increased risk of drug-drug interactions, which in turn may lead to falls, cognitive decline, medication-related problems, and even increased mortality [1620]. In nursing homes, physicians frequently prescribe drugs without a proper clinical evaluation of the patient, and staff may not be aware of this [21].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of residents are women occupying more than 70% of the nursing home beds [12]. The nursing home patients in the area of the study used 9,8 drugs on average with a variation of 0 to 30 different drugs [13]. Part-time contracted general practitioners most commonly provide the medical services in nursing homes [14], however, number of full time nursing home physicians employed by the muncicpality is raising.…”
Section: Settingmentioning
confidence: 99%